Food safety issues in Islam - Mufizur Rahman, Muhammad; Minara Khatun, Mst; Hasibur Rahman, M.; Parvin Ansary, Nazma (Health, Safety and Environment, 2020)
As regards food safety issues there is a distinct demarcation in Islam between lawful food allowed to Moslems and unlawful food not allowed to Muslims. With the increasing awareness of their Islamic dietary requirements, the Muslim consumers all the over the world now demand more information on food sources and its processing. The Islamic Rules governing food shows that they are simple and clear and can be applied easily in Muslim countries. Hygiene, sanitation and safety are important pre-requisites and Good manufacturing (GMP) or Good Hygienic Practice (GHP) is a compulsory requirement in preparing Halal food. The Global Halal Institute has a list of Halal certifiers that are approved by most Muslim countries with dietary import restrictions. Since the turn of the 21st century, there have been efforts to create organizations such as the Muslim Consumer Group that use the H-MCG symbol, with a view to identify the status of different edible and non-edible consumer products and certify food products as halal for Muslim consumers. The oldest and most well known halal certifier in the USA is Islamic Services of America. In Europe, several organizations have been created over the past twenty five years in order to certify the halal products. These companies distribute halal-certified products. Halal certification gives Muslims evidences that their ingredients and production methods have been examined and tested and declared permissible by a certification body. It also gives authentication and permits companies to export products to most Middle Eastern and South East Asian countries.